KADAR FENOLIK TOTAL, FLAVONOID TOTAL, DAN AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL DAUN BINAHONG (Anredera cordifolia Ten.Steenis) - Herawati, Irma Erika; Inayah, Ita; Dewi , Lisna (JIFI (Jurnal Ilmiah Farmasi Imelda), 2025)
Antioxidant plays an important role in the body’s defense against various diseases, because antioxidant compounds were able to prevent bad effects caused by free radicals. Phenolic and flavonoids compound are known as natural antioxidant from plants. Binahong (Anredera cordifolia) is known contain phenolic and flavonoid. The aim of this research was to determine total phenolics, flavonoids content and also antioxidant activity from extract binahong using 2,2-diphenyl-1-picrylhydrazyl (DPPH) method. The results showed that binahong ethanol extract had total phenolic 223.76 mg GAE/g and flavonoid content of 0.483 mg RE/g. Meanwhile, for antioxidant activity, IC50 for ethanol extract, ethyl acetate fraction, and water fraction were 717.27; 586.28; dan 425.81 ppm respectively. Binahong extracts and fractions are included in the weak antioxidant category.